An Experiment. - Lantry, Terry L. (The Accounting Review, 1971)
The article focuses on an experiment related to accounting course. One of the problems every teacher of auditing faces is how do you make auditing interesting to seniors who are taking the course and are graduating at the end of the term. The round of parties, the final job interview, the anticipation of graduation, all of these factors compete against the professor who teaches auditing. The auditing course assimilates everything an accounting student has learned in his business curriculum and, therefore, should be exciting and challenging to him. The senior views auditing as the last accounting course which he must suffer through in order to get a piece of paper that allows him to go out and earn a living. At Colorado State University the researchers solved the problem of lack of enthusiasm on the part of the accounting student by eliminating the traditional practice set and substituting a real audit. The opportunity to provide a real audit came about as a result of an auditing engagement performed by Price Waterhouse & Co. They audited the Associated Students of Colorado State University in June, 1968.